Differential mortality and the progressivity of social security - Shantanu Bagchi (W.E. Upjohn Institute for Employment Research, 2016)
I examine if the positive correlation between wealth and survivorship has any implications for the progressivity of Social Security's current benefit-earnings rule. Using a general-equilibrium macroeconomic model calibrated to the U.S. economy, I show that the optimal benefit-earnings link for Social Security is largely insensitive to wealth-dependent mortality risk. This is because while a more progressive benefit-earnings rule provides increased insurance for households with relatively unfavorable earnings histories, and therefore lower savings and survivorship, their relatively high mortality risk heavily discounts the utility from old-age consumption. I find that these two effects roughly offset each other, yielding nearly identical optimal benefit-earnings rules both with and without differential mortality.
Keywords: E21; E62; H55; 330; differential mortality; Social Security; mortality risk; labor income risk; incomplete markets; social insurance; general equilibrium